1998
DOI: 10.3354/meps174233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biological disturbance on diversity and structure of meiobenthic nematode communities

Abstract: Benthic mesocosm experiments have shown that subtidal macrofauna species with contrasting feedlng behaviour and mobility can alter the structure of natural subtidal meiobenthic nematode assemblages. Test macrofauna species were the bivalves Nuculoma tenuis (subsurface-deposit feeder) and Abra alba (surface-deposiWsuspension feeder) at 3 different densities and the heart urchin Brissopsis lyrifera (subsurface burrowing deposit feeder) at a single density. a and P nematode diversity were affected by disturbance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…They stressed that high species diversity can be maintained by habitat patchiness. The results of mescosm experiments of Austen et al (1998) were consistent with Intermediate Disturbance Hypothesis (Connell 1978) and the authors suggested that dominance of few species, as it is the case in our study, is important in maintaining regional diversity. Our results agree with this study, in that species diversity (H¢) and species number (S) were reduced when wind stress and discharge stress were either both low and both high.…”
Section: General Composition Of Nematode Communitiessupporting
confidence: 90%
“…They stressed that high species diversity can be maintained by habitat patchiness. The results of mescosm experiments of Austen et al (1998) were consistent with Intermediate Disturbance Hypothesis (Connell 1978) and the authors suggested that dominance of few species, as it is the case in our study, is important in maintaining regional diversity. Our results agree with this study, in that species diversity (H¢) and species number (S) were reduced when wind stress and discharge stress were either both low and both high.…”
Section: General Composition Of Nematode Communitiessupporting
confidence: 90%
“…Numerous studies have assessed the impacts of various types and intensities of disturbance on benthic communities (Pearson and Rosenberg, 1978;Heip, 1980;Rees, 1983;Zajac and Whitlach, 1982;Coull and Chandler, 1992;Hall, 1994;Austen et al, 1998;Schratzberger and Warwick, 1999;Cowie et al, 2000;Huxham et al, 2000;McCabe and Gotelli, 2000). These have established that benthic communities show a wide range of responses to disturbance, and that these responses can vary depending on the frequency and intensity of disturbance.…”
Section: Introductionmentioning
confidence: 97%
“…studying the response of meiofauna to different levels of trawling disturbance, showed a significant increase of Daptonema in areas subjected to medium disturbances. On other hand, meso-and microcosms experiments carried out by Austen et al (1998) and Schratzberger and Warwick (1999), respectively, showed that densities of Terschellingia may be negatively affected by low disturbance levels.…”
Section: Discussionmentioning
confidence: 96%